2014
DOI: 10.1186/s12879-014-0701-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of highly active antiretroviral therapy in HIV- infected Indian children

Abstract: BackgroundWith the advent of highly active antiretroviral therapy (HAART), HIV infection has become a chronic condition in children with improved survival and quality of life. Reports on long term effectiveness of non-nucleoside reverse transcriptase inhibitor based HAART in HIV-infected children in developing countries are limited.MethodsA chart review was conducted and children who received at least six months of HAART between 2004–2011 at All India Institute of Medical Sciences (AIIMS), Delhi were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Specifically, the HAZ at both ART initiation and follow up was found to be positively correlated with the CD4 percentage at follow up. Similar reports have been published thus far for adults and older children [25, 28, 29]. …”
Section: Discussionsupporting
confidence: 88%
“…Specifically, the HAZ at both ART initiation and follow up was found to be positively correlated with the CD4 percentage at follow up. Similar reports have been published thus far for adults and older children [25, 28, 29]. …”
Section: Discussionsupporting
confidence: 88%
“…Having a short duration of follow-up, advanced WHO stage at follow up visit, ART non-adherence, and TB at baseline was found to be independent predictors of first-line ART treatment failure. In this study, the median survival time was 57.7 months (95% CI 54.83, 59.77) which is longer than the findings of studies in India; 43 months, 26 a combined study in Mozambique and Uganda; 12.6 months 27 and Uganda; 26.4 months. 28 This could be explained by the improvements in the therapeutic and diagnostic measures in current visits from then and the increase in access and variety of more potent drugs nowadays than the past periods.…”
Section: Discussioncontrasting
confidence: 70%
“…Since the discovery of highly active anti-retroviral therapy (HAART), there has been improvement in virology findings, thus HIV-1-infected children can grow and thrive properly [8][9][10]. Survival rate against HIV are increasing in children worldwide and it improves the quality of life in HIV-1-infected children [9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have shown the long-term outcomes of children receiving antiretroviral therapy [8][9][10][17][18][19] but there are no reports on the successful treatment of HIV-1infected children in Indonesia. It is not easy to get an overview about the therapy efficacy in Indonesia, where only less than half of patients had a good adherence to therapy.…”
Section: Resultsmentioning
confidence: 99%